Analisis hubungan enam dimensi dalaman dan luaran motivasi perkhidmatan awam kakitangan awam Indonesia (Kajian Kes di Jakarta) - Mulyawan, Budy (2023)
The performance of civil servants is one of the most important issues to be discussed, since it may affects the image of the government and its overall management efficiency. In Indonesia, the quality of service and work performance of its civil servants in recent years have not shown satisfactory results. This has led to unsatisfactory government performance in the public service sector. Efforts to improve civil servants’ performance depend on the government's ability to identify and leverage the various forms of motivation that drive civil servants’ performance. One of the internal factor that may be able to improve civil servants’ performance is public service motivation. The main objective of this study is to examine the intrinsic and extrinsic dimensions that correlate with the public service motivation among civil servants in Jakarta. This study surveyed 951 civil servants from three different agencies with the highest income in Jakarta, namely the DKI Provincial Government Jakarta, The Directorate General of Taxes, and The Directorate General of Immigration. The informants interviewed were officers who are competent and have knowledge on the human resources issues and the implementation of public services in each respective agencies. The results of data analysis using both the quantitative and qualitative approaches showed a significant difference in the level of public service motivation among civil servants in Jakarta. Furthermore this study found that the use of prerequisite questions about the fulfillment of basic needs before answering the public service motivation questions can provide a more valid result when measuring the level of public service motivation. This study also discovered a significant correlation between attraction to public policy making, commitment to public interest and civic duty, compassion, and self-sacrifice dimensions, with the level of public service motivation among civil servants in Jakarta. The study also revealed a significant relationship between the belief in a just world dimension and the level of public service motivation. Therefore, this dimension is suitable to be applied as an additional measure on the level of public service motivation among civil servants in Indonesia. The finding also reveals that there are only four dimensions of job characteristics that have a significant correlation to public service motivation.